PHYTOCHEMICAL ANALYSIS, ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF DIFFERENT CRUDE EXTRACTS OF MARINE RED ALGA GRACILARIA CORTICATA FROM THE GULF OF MANNAR SOUTH COAST, NAVALADI, SOUTH INDIA (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
To investigate the antibacterial and antifungal activity of hexane, chloroform, ethyl acetate, acetone and methanol extracts of Gracilaria corticata J. Ag against bacterial and fungal strains viz., Bacillus subtilis, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhimurium, Vibrio cholerae, Shigella flexneri, Proteus mirabilis and Proteus vulgaris. Fungal strains Candida albicans, Candida krusei, Candida guilliermondi, Candida parapsilosis, Candida tropicalis, Candida glabrata, four dermatophytes viz., Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum gypseum and Epidermophyton flocossum. The extracts of G. corticata were extracted with different solvents viz., hexane, chloroform, ethyl acetate and methanol against bacterial and fungal strains by using disc diffusion method, MIC, MBC and MFC were determined. The ethyl acetate extract of G. corticata showed the highest antibacterial and antifungal activity against all the bacterial and fungal strains tested than the other extracts. The mean zones of inhibition produced by the extracts in agar disc diffusion assays were from 7.1 to 16.0 mm. The Minimum Inhibitory Concentrations (MIC) was between 125 and 500μg/ml, while the Minimum Bactericidal Concentrations and Minimum Fungicidal Concentrations (MFC) were between 250 and 500μg/ml. The highest mean zone of inhibition (16.0 mm) was observed in ethyl acetate extract of G. corticata against B. subtilis. The lowest MIC (125µg/ml), MBC and MFC (250µg/ml) values was observed in ethyl acetate extract of G. corticata against B. subtilis. The results suggest that the effective ethyl acetate crude extract of G. corticata showed the presence of phytochemical, terpenoids, tannins and phenolic compounds strongly than the other solvent extracts. These finding suggest that ethyl acetate crude extract of G. corticata have potential antimicrobial activity are under going further analysis to identify the active compounds currently progress.